Anàlisi contrastiva de la innovació lèxica en català i en castellà - Cabré, M. Teresa; Freixa, Judit; Solé, Elisabet (Caplletra. Revista Internacional de Filologia, 2001)
The contrastive analysis of a corpus of neologisms is an appropriate way to describe and analyse the mechanisms of lexical innovation used to update the lexicon. It also shows the degree of linguistic coincidence and helps make hypotheses on the influence of some languages on others. The synchronic study of several neologisms from the Neology Observatory highlights the degree of coincidence and divergence between Catalan and Spanish with respect to two aspects: (i) the mechanisms of innovation (morphological, semantics and borrowings) and (ii) the resulting neologisms. This analysis also allows to make some hypotheses about the influence of Spanish and other languages on Catalan.